Evaluation of the antimicrobial and cytotoxic activity of nerolidol encapsulated in a nanoliposome system - Mezzasalma, Nicolò; Spadini, Costanza; Righi, Federico; Simoni, Marica; Lamberti, Gaetano; Barba, Anna Angela; Greco, Dante; Merelli, Alessia; Bosio, Lorenzo; Cupola, Alessandro; Schiano, Emiliana; Taddei, Simone; et al. (Frontiers in Veterinary Science, 2025)
Plant-derived compounds have emerged as potential alternatives to traditional antimicrobials in livestock; however, their application may be limited by degradation in the gastrointestinal tract. Nanoliposome encapsulation offers a strategy to overcome these limitations. In this study, we investigated the effects of nerolidol encapsulation, by evaluating the antimicrobial activity of free-nerolidol (NER), nerolidol-loaded nanoliposomes (LN), and unloaded nanoliposomes (UN) (Lipobox™) using a Time-Kill assay. The cytotoxicity of these formulations was assessed through MTT assay on swine and bovine cell lines. NER was effective against MRSA, Enterococcus faecium, and Lactobacillus acidophilus at all time points, at concentrations ≥62.5, ≥15.63 and ≥1,000 μg/ml, respectively, but was ineffective against Gram-negative bacteria Conversely, LN and UN were effective against all bacteria, showing the best activity at 2,500 μg/ml. LN showed the greatest activity against MRSA up to 6 h while UN on E. faecium up to 4 h (P < 0.05). No difference between LN and UN on Salmonella Typhimurium up to 24 h and on E. coli up to 6 h at this concentration (P > 0.05) was observed. For L. acidophilus, both LN and UN were effective up to 6 h even at the lowest concentration (9.77 μg/ml). NER showed high cytotoxicity on MDBK and IPEC-J2 cells at all doses; while LN and UN were low-toxic at concentrations ≤ 1,250 μg/ml or ≤ 625 μg/ml, respectively. These results suggest that nanoliposomes themselves exhibit dose-dependent antimicrobial and cytotoxicity activity; however, when NER is encapsulated its spectrum of activity its enhanced.